Softskill profile analysis of food and beverage service sector workforce among the hotel industry in Yogyakarta area - Purnama, Elita Candra; Komariah, Kokom (Universitas Merdeka Malang, 2025)
Service quality in the hospitality industry is highly dependent on the workforce's soft skills, yet empirical data regarding the profile and mastery level of these competencies, particularly in the Food and Beverage (F&B) Service sector, remains limited despite its crucial role in addressing industry dynamics. This study aims to identify the profile and analyze the mastery level of soft skills among the F&B Service sector workforce in Yogyakarta City, focusing on five main dimensions: interpersonal skills, self-management, ethics and professionalism, collaboration and problem-solving, and innovation and initiative. The method used is quantitative descriptive through a cross-sectional survey of 48 respondents from six 3-star and 4-star hotels in the Yogyakarta City area. The questionnaire instrument used has been tested for both content and construct validity, as well as reliability, to ensure measurement feasibility. The results showed that the five main soft skills possessed by the F&B Service sector workforce in the hospitality industry in the Yogyakarta City area were in the excellent category: interpersonal skills (88.15%), self-management (87.78%), ethics and professionalism (89.10%), collaboration and problem-solving (89.33%), and innovation and initiative (86.22%), with an overall average of 88.31%. These findings interpretatively confirm that soft skills are an essential foundation for a professional workforce in the hospitality industry. The implication is that future hospitality HR development and vocational education curricula need to focus on strengthening and continuous training to maintain excellent service quality consistently.